ORIENTASI BERUSAHATANI DI DESA TONSEWER KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA - Megawati ., Sumilat; Melsje Y. Memah; Nordy F. L. Waney (Sam Ratulangi University, 2018)
The purpose of the study was to find out the orientation of farming in Tonsewer Village, West Tompaso Sub-district, Minahasa Regency. This research was conducted for five months, from November 2017 to March 2018, from preparation to formulation of research reports. Research site in Tonsewer Village, West Tompaso Sub-district, Minahasa Regency. This study uses primary data and secondary data. Primary data was obtained from interview of 72 respondents using a questionnaire. Secondary data was obtained from the Office of the Tonsewer Village in the West Tompaso Sub-district, Minahasa Regency. The method of determining the sample in this study using the simple random sampling method using Slovin formula. The results showed that based on the orientation criteria of land input farming, it was commercially oriented because > 65% of the land was self-owned, the workforce was commercially oriented because > 65% of farmers paid for outside labor and farm output was commercially oriented because > 65% of the farm selling, so it can be concluded that farmers in Tonsewer Village are commercially oriented.